High-resolution UAV Orthomosaic and DSM Dataset - Blueberry Hill (Aklavik, NWT, CA) 5 cm GSD [2022] - Mueller, Marlin M.; Thiel, Christian; Kaiser, Soraya; Lenz, Josefine; Langer, Moritz; Fritz, Oliver; Marx, Sabrina (Zenodo, 2024)
This dataset contains a high-resolution (5 cm) orthomosaic and Digital Surface Model (DSM) generated from aerial imagery captured by a DJI Mini 2 drone. The data was acquired on September 24, 2022, and covers an area of 1.77 km². The data was acquiered as part of the UndercoverEisAgenten project funded by German Federal Ministry of Education and Research together with students of Moose Kerr School, Aklavik, NWT, Canada. The processing parameters used in Metashape are detailed in the attached report.